Intellectual development disorder syndrome with congenital anomalies of type 99, faceted female (OMIM: 300968), updated mutation in the USP9X gene - A. Sh. Latypov; E. V. Proskurin; O. P. Sidorova; I. A. Vasilenko; D. V. Kassina; M. S. Bunak (Русский журнал детской неврологии)
The syndrome of mental retardation with congenital anomalies of type 99, limited to the female sex (OMIM: 300968) is an X-linked dominant disorder of the development of the central nervous system, characterized by delayed psychomotor development and mild or moderate mental retardation.In the article, a clinical case of a 2-year-old 8-month-old patient with mental retardation syndrome and type 99 congenital anomalies characteristic only of the female sex (OMIM: 300968) is presented. Due to the heterozygous carriage of a previously undescribed pathogenic variant with a reading frame shift in the X-linked USP9X gene associated with a type 99 developmental disorder with dominant inheritance, in chrX:41196714AATTG>A, ENST00000378308, C.4214_4217delATT.P.Asp1405fs. The pathogenic variant was confirmed in the child in the study of the trio by Sanger. It is absent from the parents (a new pathogenic variant). Along with cognitive impairments, the patient revealed congenital anomalies, some of which coincided with those previously described. There were also some special features: the asymmetry of the skull in the described patient was expressed in the parietal part of the skull, and not the facial one, as described in previous publications. Secondary mitochondrial disorders were revealed during the study of the activity of mitochondrial enzymes in peripheral blood lymphocytes, which are an “enzymatic mirror” of tissues, which is an indication for the appointment of energotropic drugs (succinic acid and carnitine).